2007
DOI: 10.1111/j.1447-0756.2007.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant ovarian cancer weighing 100 kg with poor prognosis

Abstract: We encountered a patient with giant ovarian cancer with a tumor weight of 100 kg. The patient's girth measured 198 cm after approximately 4 years' duration, and she complained of dyspnea and inability to walk. Adnectomy was performed with intensive intraoperative monitoring. The ovarian cancer was entirely adherent to the parietal peritoneum. However, 10 h after adnectomy, she died of massive abdominal bleeding from extremely redundant parietal peritoneum caused by disseminated intravascular coagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…Hemodynamic instability induced by fluid depletion and aortocaval decompression during removal of the cyst is also a concern. Some advocate progressive preoperative drainage to avoid the development of severe clinical hypotension [7,9]. Five potential problems have been associated with the resection of massive ovarian tumours: respiratory failure, intraoperative fluids shifts, adequate exposure, orthostatic hypotension and adynamic intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemodynamic instability induced by fluid depletion and aortocaval decompression during removal of the cyst is also a concern. Some advocate progressive preoperative drainage to avoid the development of severe clinical hypotension [7,9]. Five potential problems have been associated with the resection of massive ovarian tumours: respiratory failure, intraoperative fluids shifts, adequate exposure, orthostatic hypotension and adynamic intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the patient died of massive abdominal bleeding caused by disseminated intravascular coagulation 10 h postoperatively. Generally speaking, the majority of giant ovarian tumours are benign, borderline or of low malignant potential because when invasive cancer is present, clinical symptoms occur before the mass reaches a significant volume [7]. These huge neglected cysts can mimic other medical conditions on physical examination, like pregnancy, massive ascites, colonic volvulus and idiopathic megacolon [5], and they can give rise to various clinical complications resulting from local compression such as abdominal pain, hydronephrosis and aortocaval compression.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the patient compulsorily maintains a lateral position to prevent supine hypotension syndrome, operation handlings and anesthesia management become difficult. Such a massive tumor is likely to have feeding vessels or show adhesion, implying a risk of major bleeding [9,10]. En block removal is also associated with a possible risk of rupture during surgery [6].…”
Section: Discussionmentioning
confidence: 99%
“…Complications associated with the removal of giant ovarian tumors have been described, including massive bleeding or re-expansion pulmonary edema. 4,5,7,[9][10][11][12] To the authors' best knowledge, 22 cases of giant ovarian tumor of > 40 kg have been reported since 1970 (Table 1). A giant ovarian mucinous cystadenoma that underwent successful intraoperative drainage over 2 hours is reported, along with a review of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…1 Most cases are benign, but some cases of low-malignant-potential tumors or adenocarcinomas have been reported. [2][3][4][5][6][7] Their management, especially whether and when to drain the cysts, has been discussed over the years, but there is no clear consensus. Complications associated with the removal of giant ovarian tumors have been described, including massive bleeding or re-expansion pulmonary edema.…”
Section: Introductionmentioning
confidence: 99%